Science outreach at Madrasa Menggunakan Poster Fisika pada Materi Gelombang dan Bunyi - Pranata, Ogi Danika; Seprianto, Seprianto; Gusvina, Fadilla; Juniyati, Sintia; Dewi, Mustika Sandra (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
This science outreach activity aims to explore the effectiveness of posters as a learning medium in science education. The activity was conducted at a Madrasah Tsanawiyah, involving 23 students who participated in science learning on waves and sound using posters designed by Tadris Physics students. Before the learning session, students were asked to assess their interest in and difficulty with learning science. After the session, they provided their perceptions of using posters as a learning tool. The results indicate that the majority of students enjoy science, although some still find it challenging. Posters effectively captured students’ attention and aided their understanding of concepts, with an average positive perception score of 3.58 out of 5. However, some students still struggled to comprehend the poster content independently, highlighting the need for additional guidance from instructors. These findings align with previous research showing that posters can enhance student engagement in science learning. As a recommendation, project-based science outreach activities, such as student-created scientific posters, can be implemented to improve conceptual understanding and scientific communication skills.